Foreword - Qvarsebo, Jonas (Educare, 2016)
This issue of EDUCARE is dedicated to the fields of punk and hiphop studies. In December 14-16 2014 the network for childhood and youth studies, funded by FAS/FORTE, hosted a conference at Malmö University with the name “Politics of identity, activism and pedagogy in punk of hip-hop studies”. In this issue we present four articles based on papers and presentations from the conference.